2010
DOI: 10.1073/pnas.1008950108
|View full text |Cite
|
Sign up to set email alerts
|

Neural systems predicting long-term outcome in dyslexia

Abstract: Individuals with developmental dyslexia vary in their ability to improve reading skills, but the brain basis for improvement remains largely unknown. We performed a prospective, longitudinal study over 2.5 y in children with dyslexia (n = 25) or without dyslexia (n = 20) to discover whether initial behavioral or brain measures, including functional MRI (fMRI) and diffusion tensor imaging (DTI), can predict future long-term reading gains in dyslexia. No behavioral measure, including widely used and standardized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
391
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 426 publications
(439 citation statements)
references
References 56 publications
33
391
1
4
Order By: Relevance
“…Increased activation in less skilled readers has been attributed to overengagement, due to increased difficulty and effort necessary during reading tasks (Shaywitz et al 1998;Brunswick et al 1999;Milne et al 2002). This compensatory theory is supported by findings of more prominent hyperactivation in older, or remediated, readers (Shaywitz et al 2003;Hoeft et al 2011;Richlan et al 2011;Barquero et al 2014).…”
Section: Introductionsupporting
confidence: 61%
“…Increased activation in less skilled readers has been attributed to overengagement, due to increased difficulty and effort necessary during reading tasks (Shaywitz et al 1998;Brunswick et al 1999;Milne et al 2002). This compensatory theory is supported by findings of more prominent hyperactivation in older, or remediated, readers (Shaywitz et al 2003;Hoeft et al 2011;Richlan et al 2011;Barquero et al 2014).…”
Section: Introductionsupporting
confidence: 61%
“…that the RH is utilized by populations having reading deficits raises the question of whether the role of RH is only compensatory or whether it can independently support reading on its own when the LH is not available [9,40]. The findings of previous research that has investigated these questions (with a total of 7 patients across all these published studies) suggest heterogeneity in reading abilities following left hemispherectomy [19,20,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Although language competence of the RH is now widely recognized [7], its involvement in reading in healthy populations is traditionally thought to be limited to higher-order skills, such as pragmatics, nonliteral language, and prosody, in addition to some role in semantic interpretation at the single-word level. Interestingly, imaging studies have suggested an increased involvement of the RH in struggling readers -including both those with developmental deficits (e.g., dyslexia) and those having acquired abnormalities (e.g., poststroke) on the left side [8][9][10][11][12][13]. The compensatory nature of RH involvement in these readers and an understanding of what possible advantages it offers for reading recovery remain unclear partly because of a lack of information regarding the potential of the isolated RH in the development of phonological processing and reading skills.…”
Section: Introductionmentioning
confidence: 99%
“…44, 50, and 64). Furthermore, it has been shown that right prefrontal activation in children with a diagnosis of DD can significantly predict reading gains 2.5-y later, indicating that these compensatory mechanisms can function as part of the reading network (64).…”
mentioning
confidence: 99%